1998
DOI: 10.1038/33198
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of polyadenylate-binding protein with the eIF4G homologue PAIP enhances translation

Abstract: In the initiation of translation in eukaryotes, binding of the small ribosomal subunit to the messenger RNA results from recognition of the 5' cap structure (m7GpppX) of the mRNA by the cap-binding complex eIF4F. eIF4F is itself a three-subunit complex comprising the cap-binding protein eIF4E, eIF4A, an ATP-dependent RNA helicase, and eIF4G, which interacts with both eIF4A and eIF4E and enhances cap binding by eIF4E. The mRNA 3' polyadenylate tail and the associated poly(A)-binding protein (PABP) also regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
343
1
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 349 publications
(356 citation statements)
references
References 27 publications
9
343
1
3
Order By: Relevance
“…(85) It forms complexes of 1:1 stochiometry with PABP, (86) interacts with eIF4A, and was reported to co-activate cap-dependent translationdespite having no eIF4E binding motif. (85) By contrast, Paip2 is a small acidic protein that acts as a translational repressor, with a preferential effect on the translation of polyadenylated mRNAs. (87) Two molecules of Paip2 can simultaneously bind to PABP.…”
Section: Assembly Of the 80s Ribosomementioning
confidence: 99%
“…(85) It forms complexes of 1:1 stochiometry with PABP, (86) interacts with eIF4A, and was reported to co-activate cap-dependent translationdespite having no eIF4E binding motif. (85) By contrast, Paip2 is a small acidic protein that acts as a translational repressor, with a preferential effect on the translation of polyadenylated mRNAs. (87) Two molecules of Paip2 can simultaneously bind to PABP.…”
Section: Assembly Of the 80s Ribosomementioning
confidence: 99%
“…The sequence of the full-length protein shared strong homology to eIF4G (58) and placed this novel gene within this family of scaffold proteins, which has since expanded to also include the PAIPs. 65,66 In addition, detailed sequence alignments showed that the region corresponding to the rescued miniprotein was less conserved within the family members ( Figure 1). Therefore, it was assumed that this miniprotein acted in a dominant-negative manner selectively counteracting the function of the endogenous DAP5 (and not the other family members), thus conferring some resistance to IFN-g during the selection procedure.…”
Section: Dap5/p97/nat1 -The Discovery Of the Gene And Initial Structumentioning
confidence: 99%
“…Its mRNA possesses a relatively long 5 0 UTR and a single ORF starting at a GUG initiation codon, which resides within the consensus sequence for non-AUG initiators. [60][61][62][63] The homology to eIF4G 65,66 was restricted to the central segment of eIF4GI/II, which corresponds to the region that binds to eIF4A and eIF3, necessary elements of the translation initiation complex. Interestingly, the N-terminal part of eIF4GI/GII, which mediates the interaction with the mRNA cap structure by direct binding to eIF4E, is completely missing from DAP5 protein (Figure 1).…”
Section: Dap5/p97/nat1 -The Discovery Of the Gene And Initial Structumentioning
confidence: 99%
See 2 more Smart Citations